Pomen izobraževanja o komuniciranju v paliativni oskrbi - Globočnik Papuga, Petra (Obzornik zdravstvene nege, 2007)
Palliative care is are integrated care for seriously ill patients that involves physical, psychological, social and spiritual needs of patients and their relatives. Good communication is of vital importance and can be achievedby specific training, practical work and work on oneself. The article is based on a qualitative research carried out among the nurses who meet seriously ill and dying patients daily at The University Clinic of Pulmonary and Allergic Diseases Golnik. The nurses and technicians involved in the research have expressed the need to obtain additional knowledge about communication, communication evaluation, time planning for conversation for active support to the dying and their relatives and to settle conditions in palliative care on the national level. Before training they experienced personal distress and fear of patients' and their relatives' reactions more frequently and they avoided having a conversation with them. The results of the research show that training is important, that the knowledge obtained at the workshops `Communicating bad news' is used in practical work, that motivation for communication with seriously ill and dying patients, for self-training and for co-workers' communication have increased. Professional relation and understanding of patients' and their relatives' reactions have improved.
Keywords: communication; education; Education, Nursing, Continuing; izobraževanje; Izobraževanje, zdravstvena nega nadaljevalno; komuniciranje; Medicinska sestra-bolnik, odnosi; nega bolnika; Nurse-Patient Relations; Paliativna oskrba; Palliative Care; zdravstveni delavci